PERSPECTIVES ON TEACHING ENGLISH AND TRANSFORMING VALUES OF CHARACTER TO BROADEN STUDENTS HORIZON - Firman Parlindungan (Universitas Islam Negeri Banda Aceh, 2014)
A great demand of mastering English in globalization era has made English education in Indonesia valuable and popular. Problems in classroom, quality of teachers, teaching strategies and media are a plethora of topics that have been concerns to be developed. On another front, there is an effort to shape students’ character building which enables them to master social competence with the expected behavior and moral capacity. Students can be trained some certain good characters within the implementation of language teaching. By taking these two variables into account, success of learning can be achieved not only in language mastery, but also in students’ character.